Gamification in spoken language pedagogy: Indonesian EFL teachers - Nurlaila, Nurlaila; Wulyani, Anik Nunuk; Halisiana, Hermiyanti Tri (Journal on English as a Foreign Language, 2024)
Gamification enhances student engagement and learning through problem-solving, storytelling, competition, and rewards, but its success depends on having well-trained teachers. Thus, investigating educators' perspectives on using gamification, particularly in teaching speaking, is essential. The study aims to explore Indonesian EFL teachers